Prospective evaluation of ERCP performance in an Italian regional database study. Issue 7 (July 2019) - Mariani, Alberto; Segato, Simone; Anderloni, Andrea; Cengia, Gianpaolo; Parravicini, Marco; Staiano, Teresa; Tontini, Gian Eugenio; Lochis, Davide; Cantù, Paolo; Manfredi, Guido; Amato, Arnaldo; Bargiggia, Stefano; et al.
Abstract: Background: Prospective studies about endoscopic retrograde cholangio-pancreatography (ERCP) in a community setting are rare. Aim: To assess success and complication rates of routinely-performed ERCP in a regional setting, and the priority quality indicators for ERCP practice. Methods: Prospective region wide observational study on consecutive patients undergoing ERCP during a 6-month period. A centralized online ERCP questionnaire was built and used for data storage. Primary quality indicators provided by the American Society of Gastrointestinal Endoscopy (ASGE) were considered. Results: 38 endoscopists from 18 centers performed a total of 2388 ERCP. The most common indication for ERCP was choledocholitiasis (54.8%) followed by malignant jaundice (22.6%). Cannulation of the desired duct was obtained in 2293 cases (96%) and ERCP was successful in 2176 cases (91.1%). Success and ERCP difficulty were significantly related to the experience of the operator (p = 0.001 and p < 0.001, respectively). ERCP difficulty was also significantly related to volume centers (p < 0.01). The overall complication rate was 8.4%: post-ERCP pancreatitis (PEP) occurred in 4.1% of procedures, bleeding in 2.9%, infection in 0.8%, perforation in 0.4%. Mortality rate was 0.4%. All the ASGE priority quality indicators for ERCP were confirmed. Conclusions: The procedural questionnaire proved to be an important tool to assess and verify the quality of routinely-performed ERCP performance in a community setting.